Penentuan Kelayakan Kredit Dengan Algoritma Naïve Bayes Classifier: Studi Kasus Bank Mayapada Mitra Usaha Cabang PGC - Nia Nuraeni (Universitas Bina Sarana Informatika, 2017)
In analyzing a credit sometimes a less accurate credit officer in credit analysis, so that it can lead to increased bad debts. Classification data mining algorithms are widely used to determine the credit worthiness of one Naive Bayes classifier, NBC superior in increasing the value of high accuracy but weak in the selection of attributes. After testing Naive Bayes classifier algorithm the results obtained is Naive Bayes classifier algorithm produces an accuracy of 89.33% and AUC values for 0.955.Keyword: Credit Analysis, Naive Bayes ClassifierAlgorithm